A Field Test of Web-Based Screening for Dry Eye Disease to Enhance Awareness of Eye Problems Among General Internet Users: A Latent Strategy to Promote Health - Kawashima, Motoko; Uchino, Miki; Kawazoe, Takashi; Kamiyashiki, Masaaki; Sano, Kokoro; Tsubota, Kazuo (JMIR Publications, 2013)
BackgroundA Web-based self-check system including a brief questionnaire would seem to be a suitable tool for rapid disease screening. ObjectiveThe purpose of this preliminary study was to test a Web-based self-screening questionnaire for drawing attention to dry eye disease among general Internet users and identifying those with a higher risk of developing the condition. MethodsA survey website was launched and used to recruit participants from general Internet users. In the first phase, volunteers were asked to complete a Web-based self-screening questionnaire containing 12 questions on dry eye symptoms. The second phase focused on the respondents who reported five or more dry eye symptoms and expressed their intention to seek medical attention. These participants performed the Schirmer test, for evaluating tear production, and completed a paper-based lifestyle questionnaire to provide relevant background data. ResultsOf the 1689 visitors to the website, 980 (58.0%) volunteers completed the Web-based self-screening questionnaire. Among these, 355 (36.2%) respondents reported five or more dry eye symptoms. Then, 99 (27.9%) of the symptomatic participants performed the Schirmer test and completed the paper-based lifestyle questionnaire. Out of these, 32 (32.2%) had abnormal tear production (≤5 mm). ConclusionsThe proposed Web-based self-screening questionnaire seems to be a promising tool for raising awareness of dry eye disease among general Internet users and identifying those with a higher risk of developing the condition, although further research is needed to validate its effectiveness.